Enhanced charge-discharge characteristics of RuO2 supercapacitors on heat-treated TiO2 nanorods - Ahn, Young Rack; Park, Chong Rae; Jo, Seong Mu; Kim, Dong Young (AMER INST PHYSICS, 2007)
Electrochemical capacitors based on RuO2 were prepared onto electrospun TiO2 nanorods. Further heat treatment of the TiO2 at 800 degrees C under nitrogen was found to greatly improve the electrochemical performance of the RuO2 electrodes, especially at fast charge-discharge rates. The specific capacitance was found to decrease by only 33% when the scan rate increased from 10 to 1000 mV s(-1) (from 687 to 460 F g(-1)). The characteristic response time of the RuO2 electrode was found to be 0.15 s when a heat-treated TiO2 substrate was used, which is 20 times better than that of the pristine TiO2 used. (c) 2007 American Institute of Physics.